Combined noise and echo reduction in hands-free systems a survey. - Jeannes, W.L.B.
The modern telecommunications field is concerned with freedom and, in this context, hands-free systems offer subscribers the possibility of talking more naturally, without using a handset. This new type of use leads to new problems which were negligible in traditional telephony, namely the superposition of noise and echo on the speech signal. To solve these problems and provide a quality that is sufficient for telecommunications, combined reduction of these disturbances is required. This paper presents a summary of the solutions retained for this dual reduction in the context of mono-channel and two-channel sound pick-ups
Keywords: Hands-free systems; Mobile radio; Mono-channel sound pick-ups.; Speech signal; Two-channel sound pick-ups.; Combined noise/echo reduction systems